Comparison of Conventional and Novel Pre-treatment Methods for Bioethanol Production from Fruit and Vegetable Wastes - Keskin, Tugba (Chemical and Biochemical Engineering Quarterly, 2020)
In this study, novel and conventional techniques for the production of bioethanol from fruit and vegetable wastes (FVWs) by yeast and bacterial fermentation were investigated experimentally. Different pretreatment techniques (acid, heat, acid/heat, and microwave) for yeast fermentation were compared. Maximum ethanol concentrations of 11.7 and 11.8 g L–1 were observed from acid/heat and microwave pretreatment, respectively, by using Saccharomyces cerevisiae. On the other hand, biochar production from FVWs and syngas fermentation from the waste gas of this process were integrated. From waste gas with 12 % CO content, 5.5 g L–1 and 2.5 g L–1 ethanol production was observed by using anaerobic mixed culture and Clostridium ljungdahlii, respectively. The overall results emphasize the potential of bioethanol production from FVWs by economically feasible and environmentally friendly methods.